Bladder Cancer Immunotherapy: BCG and Beyond - Eric J. Askeland; Mark R. Newton; Michael A. O’Donnell; Yi Luo (Advances in Urology)
Mycobacterium bovis bacillus Calmette-Guérin (BCG) has become the predominant conservative treatment for nonmuscle invasive bladder cancer. Its mechanism of action continues to be defined but has been shown to involve a T helper type 1 (Th1) immunomodulatory response. While BCG treatment is the current standard of care, a significant proportion of patients fails or do not tolerate treatment. Therefore, many efforts have been made to identify other intravesical and immunomodulating therapeutics to use alone or in conjunction with BCG. This paper reviews the progress of basic science and clinical experience with several immunotherapeutic agents including IFN-α, IL-2, IL-12, and IL-10.